Pengaturan Dan Praktek Praperadilan Tindak Pidana Pajak Di Indonesia - Sofian, Ahmad; Hasibuan, Batara Mulia (Jurnal Hukum & Pembangunan, 2020)
Pretrial is an institution to control and correct law enforcement which are deemed to have violated mechanisms established in procedural laws. The correction is not aimed to look into the aspects of the alleged criminal case but determine whether “rules of the game” established in the formal criminal law have been implemented properly or not. In practice, tax payers being involved in tax criminal cases often file pretrial motion although tax investigators actually have applied the principles of formal criminal law in legal measures they take. There are often different interpretations of laws and regulations used in pretrial institution for tax crimes. Therefore, it is recommended to strengthen civil servant investigators of the Directorate General of Taxation by improving their skills and technical capacity in the investigation process of tax crimes and develop a Standard Operating Procedure through Regulation of the Minister of Finance on the Determination of the Suspect, Search and Confiscation so that legal measures that they take will be more measurable and the number of suspects of tax crimes who will file pretrial motion will decrease. Or, when they file pretrial judges will make the best decision for their cases.